Anaerobic digestion of Crassulacean Acid Metabolism plants: Exploring alternative feedstocks for semi-arid lands. (February 2020) - Lueangwattanapong, Khemmathin; Ammam, Fariza; Mason, P. Michael; Whitehead, Caragh; McQueen-Mason, Simon J.; Gomez, Leonardo D.; Smith, J. Andrew C.; Thompson, Ian P.
Highlights: Methane yields of 5 selected CAM plants were equivalent to that of maize. Agave angustifolia Haw. produced the highest methane yield of all CAM substrates. Lower lignin in CAM plants as compared to maize resulted in a faster VFA production. Rumen fluid could play an important role in the hydrolysis step. CAM plants could represent other viable new feedstocks for biogas production. Abstract: In this work, five Crassulacean Acid Metabolism (CAM) species from the five different genera ( Agave, Ananas, Euphorbia, Kalanchoe, and Opuntia ) were selected as alternative feedstocks and their biochemical methane potentials (BMP) were investigated. Batch assays were performed using sludge and rumen fluid as inocula under uncontrolled pH and at mesophilic temperature (39 °C). Mean methane yields from the CAM plants inoculated with AD sludge ranged from 281 to 382 ml/gVS. These values were not significantly different from the methane yield obtained from maize, a feedstock for biomethane and volatile fatty acid (VFA), suggesting that CAM plants may be viable as bioenergy crops on poor-quality soils in areas with low rainfall that are unsuitable for cultivation of food crops.